Dark night : walking with McCahon - Edmond, Martin (Auckland University Press, 2011)
"In 1984, in the palm grove in Sydney's Botanic Gardens, the artist Colin McCahon went missing. He was found by police early next morning in Centennial Park ... Martin Edmond walks in Colin McCahon's footsteps, past pubs and monuments, art galleries and churches, barracks and parks: to accompany him some way into the darkness of his end"--Back cover